Biomechanics of the long jump: some wider applications - Hay, G. S.
For the past 3 years, members of the Sports Biomechanics Laboratory at the University of Iowa have been participating in the Elite Athlete Project initiated and sponsored by the United States Olympic Committee. Our responsibility in this project, designed to provide scientific support services to coaches and athletes preparing for the Olympic Games, has been the men's and women's long jump and the triple jump events in athletics. During the first 2 years of the project our efforts were directed toward providing appropriate information and recommendations for selected athletes preparing for the Olympic Games in Los Angeles. With that task completed, the thrust of our efforts has now shifted to the conduct of original research intended to extend our knowledge of the techniques involved. As a prelude to the development of a long-term research program to that end, we have recently conducted a fairly comprehensive review of the scientific and coaching literature on the techniques used in the long jump (Hay, 1986). The purposes of the present paper are to draw your attention to some papers and aspects of long jump technique that have not been accorded the attention they deserve from sport biomechanists and to raise some questions of a relatively far-reaching nature concerning the methods used to gather and analyze data in sports biomechanics research.